6v+6=2(v-1)

Simple and best practice solution for 6v+6=2(v-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6v+6=2(v-1) equation:


Simplifying
6v + 6 = 2(v + -1)

Reorder the terms:
6 + 6v = 2(v + -1)

Reorder the terms:
6 + 6v = 2(-1 + v)
6 + 6v = (-1 * 2 + v * 2)
6 + 6v = (-2 + 2v)

Solving
6 + 6v = -2 + 2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-2v' to each side of the equation.
6 + 6v + -2v = -2 + 2v + -2v

Combine like terms: 6v + -2v = 4v
6 + 4v = -2 + 2v + -2v

Combine like terms: 2v + -2v = 0
6 + 4v = -2 + 0
6 + 4v = -2

Add '-6' to each side of the equation.
6 + -6 + 4v = -2 + -6

Combine like terms: 6 + -6 = 0
0 + 4v = -2 + -6
4v = -2 + -6

Combine like terms: -2 + -6 = -8
4v = -8

Divide each side by '4'.
v = -2

Simplifying
v = -2

See similar equations:

| x+28=52 | | 5+3(x-4)=2(9+1) | | -2(3x-4)+8x-5= | | 2x+x=972 | | -4x^2-10x+3=0 | | x/3+2=x/2 | | 6x+7=2x-3 | | 1.6+x-3.7=-3+5.2 | | 55+4.75w=49.5+4.95w | | 3(d-8)+10= | | 5x-15/6-x=1-x/9 | | 3x+5(x+2)=62 | | 7x-3x+x-5+2x= | | 6x^2-8x+10=0 | | x^2+24xy+144y^2= | | 5g-5-g-5g= | | 3(x+2)+9=3x+8 | | 4+6=-9+7 | | m-7m-3m-5= | | 2+7+x=16 | | -4x^2-9x-4=0 | | 4x+3.2=8.8 | | 5(x-3)+2=3x+2(-5+x) | | 2+(x+4)+8x=8 | | f(x)=-4x^2-9x-4 | | -5-(-30)=x/9 | | -5(4y-6)-y=-2(y-3) | | 4t-8=10 | | -4(8x+5)-6=-32x-26 | | 11.7+x-8.4=3.7 | | 4(5x-10)=20(x-10) | | 2(tx-8)-4x=10 |

Equations solver categories